PERSUASIVE MASTERY EXPLORING A MUSLIM CELEBRITY PODCASTER'S APPEALS IN 'LIGHT UPON DARKNESS' - Abdul Latif @ Bapoo, Lilisuriani (IIUM PRESS, 2024)
This study explores the persuasive appeals of logical, emotional, and credibility appeals employed in the podcast series "Light Upon Darkness" by a prominent Muslim celebrity turned influencer. Thematic analysis using elements from the Toulmin Model, Maslow’s Hierarchy of Needs, and Aristotle’s Rhetoric of Ethos reveals that the podcaster employs a diverse approach, utilizing some elements of the Toulmin Model to strengthen logic, integrating all of Maslow’s Hierarchy of Needs to evoke emotional resonance with the audience and establishes credibility by sharing personal background, life experiences, expertise, and thoughts while showing respect to the audience. These findings offer insights into the dynamics of persuasive communication in podcasting and contribute to a broader understanding of the role of appeals in shaping effective communication within the digital realm.